Evaluation of Lignans from Piper cubeba against Schistosoma mansoni Adult Worms: A Combined Experimental and Theoretical Study - Parreira, Renato L. T.; Costa, Eveline S.; Heleno, Vladimir C. G.; Magalhaes, Lizandra G.; Souza, Julia M.; Pauletti, Patricia M.; Cunha, Wilson R.; Januario, Ana H.; Simaro, Guilherme V.; Bastos, Jairo K.; Laurentiz, Rosangela S. [UNESP]; Kar, Tapas; et al. (Wiley-Blackwell, 2019)
Six dibenzylbutyrolactonic lignans ((-)-hinokinin (1), (-)-cubebin (2), (-)-yatein (3), (-)-5-methoxyyatein (4), dihydrocubebin (5) and dihydroclusin (6)) were isolated from Piper cubeba seed extract and evaluated against Schistosoma mansoni. All lignans, except 5, were able to separate the adult worm pairs and reduce the egg numbers during 24 h of incubation. Lignans 1, 3 and 4 (containing a lactone ring) were the most efficient concerning antiparasitary activity. Comparing structures 3 and 4, the presence of the methoxy group at position 5 appears to be important for this activity. Considering 1 and 3, it is possible to see that the substitution pattern change (methylenedioxy or methoxy groups) in positions 3 ' and 4 ' alter the biological response, with 1 being the second most active compound. Computational calculations suggest that the activity of compound 4 can be correlated with the largest lipophilicity value.
Keywords: Schistosoma mansoni; Piper cubeba; dibenzylbutyrolactonic lignans; lipophilicity; natural products; biological activity; phytochemistry